POLITENESS STRATEGIES IN UZBEK AND ENGLISH: A CROSS- LINGUISTIC PRAGMATIC STUDY - Abdullaeva Gulkhayo Ulugbekovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Politeness is a fundamental aspect of human communication, reflecting social norms,  cultural  values,  and  interpersonal  relationships.  This  paper  investigates politeness strategies in Uzbek and English, focusing on how speakers convey respect, make requests, and perform speech acts in context. Uzbek, as a language with rich morphological markers and honorific forms, contrasts with English, which relies on modal verbs, hedging, and indirect phrasing. Through comparative analysis, the study highlights  the  influence  of  culture  on  pragmatic  choices,  identifies  patterns  of directness  and  indirectness,  and  demonstrates  how  linguistic  structures  shape communication strategies. The findings contribute to cross-linguistic understanding and provide insights for second-language teaching and intercultural communication.